Wound-Healing Potential of Cucurbita moschata Duchesne Fruit Peel Extract in a Rat Model of Excision Wound Repair - Saba Shaygan; Sajad Fakhri; Gholamreza Bahrami; Khodabakhsh Rashidi; Mohammad Hosein Farzaei (Hindawi Limited, 2021)
Background and Aim. Pumpkin (Cucurbita moschata Duchesne) is a medicinal plant with different pharmacological effects such as antioxidant, antidiabetic, hepatoprotective, and anticancer effects. In the present study, we aimed to investigate wound-healing activity of pumpkin fruit peel in a rat model of excision wound repair. Materials and Methods. Hydroalcoholic extractions of pumpkin fruit peel were obtained and used to prepare two different cold cream-based formulations, namely, 10% and 20% pumpkin peel extracts (PPEs). These formulations, phenytoin cream, and cold cream were topically used once daily for 14 days to compare their wound-healing effects in a rat model of excision wound repair. Wound sizes were monitored at different intervals. Skin tissue samples were subject to H&E staining for histopathological analysis. Blood samples were also taken on day 14 to measure serum levels of nitrite. Results. Both 10% and 20% PPE formulations resulted in a significant reduction of wound sizes compared to positive and negative controls. Wound closure rate was estimated to be higher in 20% PPE-treated rats. According to histopathological analysis, treatment with 20% PPE improved parameters associated with efficient wound repair, including better regeneration of epidemic layer, higher density of dermis collagen fibers, and lower presence of inflammatory cells. Also, both formulations lowered serum concentrations of nitrite. Conclusion. Given the obtained data from our study, the hydroalcoholic extract of Cucurbita moschata Duchesne fruit peel is proposed to be effective in accelerating the process of excision wound repair partly due to its antioxidant effect in terms of decreasing nitrite concentration.